Pengaruh Kualitas Pelayanan terhadap Kepuasan Konsumen - Sari, Riska Nindia; Darajat, Anwar Hakim; Ningsih, Niken Ria (Universitas Islam Balitar, 2022)
Seeing how the effect of service quality in this study on customer satisfaction at PT. Source Jaya Lariska. This study used a total population of 20 people and because the population was less than 100, the respondents who would be given a questionnaire (number of samples) were also as many as the total population of 20 people. Instrument tests used in the data analysis process are divided into validity and reliability tests. Normality and heteroskedasticity tests are also carried out which are included as tests of classical assumptions. Finally, hypothesis testing will be carried out, namely using the t test. The results obtained are significantly the quality of service has an influence on customer satisfaction. It is proven on the basis of the regression test results with a signification value of 0.048 < 0.05.